Efektivitas Program SIAP (Sehat, Inovatif, Aman, Pakai) Quick Response Code Indonesian Standard (QRIS) untuk Mendukung Inklusi Keuangan Digital di Pasar Badung, Kota Denpasar - Putu Sartini; I Putu Dharmanu Yudharta; Putu Eka Purnamaningsih (Business and Investment Review, 2023)
The SIAP QRIS program is a Bank Indonesia program to standardize a QR code-based payment system, which originally came from different QR codes. The SIAP QRIS program aims to encourage transaction efficiency, accelerate digital financial inclusion, advance MSMEs which can ultimately drive economic growth for developed Indonesia. The researcher limited this research to Pasar Badung, Denpasar City. In its implementation, there are still problems originating from program subjects, namely Bank Indonesia, the government, Perumda Pasar Sewakadarma Pasar Badung Unit, and BPD. As well as program objects, namely market traders who have not and have used QRIS and the public (consumers). The purpose of this research is to obtain empirical evidence regarding the effectiveness of the SIAP QRIS program so as to be able to improve or enhance strategies and programs in deploying QRIS. This study uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The results of related research were analyzed using five aspects according to Sutrisno, namely program understanding, right on target, on time, goal achievement, and real changes which show that the SIAP QRIS program in Pasar Badung is not optimal because its application is not in accordance with the original purpose, there is no courage to oblige traders using QRIS, merchants who are not aware of the existence of the program, the public (consumers) continue to use cash payments, not all merchants use QRIS, many perceived obstacles/obstacles, no merchant achievement targets, no blueprints, and no program to increase interest or motivation